QR Code Based Event Management System - Rajendran , Jeyapriya; Hamzah, Mohd Hamdi Irwan (Applied Information Technology And Computer Science, 2021)
Nowadays many companies are increasing their services on event planning in order to manage event using modern technology. It is difficult to manage event using manual methods by witting manually on spreadsheet and paper documents. Due to that, QR code based event management is developed. This application development can be a platform to manage and promote the events conducted by Chiteeram Solution Sdn.Bhd. This application has admin and user side. The user side consists of nine modules that are registration, login, update profile module, view events, add to cart, book events, generate QR code, view history, settings and logout. The admin side consists of nine modules that are login, create event, update event, delete event, view user profile, scan QR code, generate report and sign out. The physical design of the application constructed using a mobile-based technology, which are Android Studio, Firebase database and Java language. The methodology used in this application system is Object Oriented System Development (OOSD) involves four phases such Object-Oriented Requirement Analysis, Object-Oriented Design, Object-Oriented Implementation and Object-Oriented Testing. Analysis and design of the proposed project done using UML diagrams, data dictionary and interface design. The application will make it easier for the management to implement to their business and manage customer’s data